Using expectation and confirmation theory to determine customer loyalty among postpaid users - Mat Ali, Syukrina Alini; Wan Jusoh, Wan Jamaliah; Adewale, Abideen Adeyemi (R.K. Sharma, Institute of Medico-Legal Publications, 2018)
In developing countries, the rate of mobile network subscription is slowing down due to market saturation. Thus, acquiring new customers is a challenge for the service provider. Hence, it is vital to raise customer loyalty in mobile service providers for the purpose of maintaining customers. This paper aims to determine the factors which explain customer loyalty and satisfaction among users of mobile postpaid services. Building from the expectations and confirmation theory using the survey method of positivist research, data was collected from 338 subscribers of Digi, Maxis and Celcom located in Klang Valley, Malaysia. The data was analysed using SEM_PLS Version 3 and the result has generally revealed the significant relationship between all variables. Further analysis revealed that service expectation and performance, for example network quality (i.e. first time dial, no cut on line, etc.) were significant customer expectations when subscribing to a service provider. The finding provides further input and understanding for service providers to offer better services to their subscribers in order to satisfy and retain customers longer.